2020
DOI: 10.1021/acs.nanolett.9b05340
|View full text |Cite
|
Sign up to set email alerts
|

Modular Acid-Activatable Acetone-Based Ketal-Linked Nanomedicine by Dexamethasone Prodrugs for Enhanced Anti-Rheumatoid Arthritis with Low Side Effects

Abstract: Given the physically encapsulated payloads with drug burst release and/or low drug loading, it is critical to initiate an innovative prodrug strategy to optimize the design of modular nanomedicines. Here, we designed modular pH-sensitive acetone-based ketal-linked prodrugs of dexamethasone (AKP-dexs) and formulated them as nanoparticles. We comprehensively studied the relationships between AKP-dex structure and properties, and we selected two types of AKP-dex-loaded nanoparticles for in vivo studies on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…Dexamethasone (Dex) is a synthetic glucocorticoid (GC) used widely for treating inflammatory and autoimmune diseases [ 1 , 2 ]. However, chronic Dex treatment is associated with adverse effects, including decreased bone mineral density and microarchitecture porosity, eventually leading to glucocorticoid-induced osteoporosis (GIOP) and osteonecrosis [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone (Dex) is a synthetic glucocorticoid (GC) used widely for treating inflammatory and autoimmune diseases [ 1 , 2 ]. However, chronic Dex treatment is associated with adverse effects, including decreased bone mineral density and microarchitecture porosity, eventually leading to glucocorticoid-induced osteoporosis (GIOP) and osteonecrosis [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the interplay of NO and CO in living organisms has been known for decades, [7] the simultaneous modulation of the concentrations of NO and CO for therapeutic purpose remains elusive. Moreover, recent studies revealed that macromolecular prodrugs were more efficient for RA treatment due to the extravasation through leaky vasculature and subsequent inflammatory cell‐mediated sequestration (ELVIS) in the arthritis joints [4a, 8] …”
Section: Methodsmentioning
confidence: 99%
“…We have summarized the details of the inflammatory stimulus used for the development of bio-responsive delivery system in Table 4 107 , 108 , 109 , 110 , 111 , 112 . This section highlights recent advances in the application of stimulus-responsive drug delivery systems in RA treatments ( Table 5 ) 19 , 94 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 .…”
Section: Functional Delivery Strategies In Ra Treatmentmentioning
confidence: 99%